Get expert insights and community-driven knowledge on IDNLearn.com. Discover comprehensive answers to your questions from our community of experienced professionals.
Sagot :
Answer:
[tex]\left(x+1\right)\left(x-2\right)\left(x+2\right)(x +2 - 4i)(x +2 + 4i)[/tex]
Step-by-step explanation:
Given
[tex]f(x) = x^5 + 5x^4 + 20x^3 - 96x - 80[/tex]
[tex]Zeros: -2, -1, 2[/tex]
Required
Factorization of f(x)
The given zeros imply that:
[tex]x=-2[/tex] [tex]x =-1[/tex] [tex]x = 2[/tex]
This gives:
[tex]x + 2 =0[/tex] [tex]x + 1 = 0[/tex] [tex]x - 2 = 0[/tex]
So, some factors are:
(x + 2), (x + 1) and (x - 2)
Divide f(x) by the factors, to get the other factors:
[tex]\frac{x^5 + 5x^4 + 20x^3 - 96x - 80}{(x + 2)(x + 1) (x - 2)}[/tex]
Using a factorization calculator, we have:
[tex]\frac{\left(x+1\right)\left(x-2\right)\left(x+2\right)\left(x^2+4x+20\right)}{(x + 2)(x + 1) (x - 2)}[/tex]
Cancel out common terms
[tex]x^2+4x+20[/tex]
Using quadratic formula, we have:
[tex]x = \frac{-b \± \sqrt{b^2 - 4ac}}{2a}[/tex]
Where
[tex]a = 1; b =4; c = 20[/tex]
[tex]x = \frac{-4 \± \sqrt{4^2 - 4*1*20}}{2*1}[/tex]
[tex]x = \frac{-4 \± \sqrt{16 - 80}}{2*1}[/tex]
[tex]x = \frac{-4 \± \sqrt{-64}}{2}[/tex]
Using complex notation
[tex]\sqrt{-64}= 8i[/tex]
So:
[tex]x = \frac{-4 \± 8i}{2}[/tex]
Simplify the fraction
[tex]x = -2 \± 4i[/tex]
Split
[tex]x = -2 + 4i \ or\ x = -2 - 4i[/tex]
Equate to 0
[tex]x +2 - 4i = 0 \ or\ x +2 + 4i = 0[/tex]
The other factors are: (x +2 - 4i) and (x +2 + 4i)
Hence, the factorization of f(x) is:
[tex]\left(x+1\right)\left(x-2\right)\left(x+2\right)(x +2 - 4i)(x +2 + 4i)[/tex]
We value your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Find clear answers at IDNLearn.com. Thanks for stopping by, and come back for more reliable solutions.